Evaluation Untreated caries lesions in school children of a public school in the district of Ate – Lima - Sánchez-Sandoval, Gabriela Aracely (2023)
GObjective: To evaluate the prevalence of untreated dental caries using the pufa+PUFA index and its association with age and sex in schoolchildren aged 10 to 12 years in a public educational institution. Materials and methods: The study was descriptive, observational and cross-sectional. The data were obtained through the epidemiological survey of the period 2019, the registration was performed through the pufa+PUFA index. The relationship of variables was verified by means of Fisher's exact test. Results: A total of 136 schoolchildren aged 10 to 12 years were evaluated, 72 of whom were girls compared to 64 who were boys. The prevalence rate of untreated dental caries was 22%. At the pufa+PUFA index, the frequency was higher in the age of 11 years (9.6%) and in the male sex with (14%). In addition, no relationship was found between the study variable with age (p=0.71) and sex (p=0.179). Conclusions: No association was found between untreated dental caries and the variables age and sex in the population evaluated.